MORALISTICS AND PSYCHOMORALISTICS a unified cognitive science of moral intuition. - Wood, Graham ([S.l.] : ROUTLEDGE, 2022)
This book brings together three distinct research programmes in moral psychology - Moral Foundations Theory, Cognitive Adaptations for Social Exchange, and the Linguistic Analogy in Moral Psychology - and shows that they can be combined to create a unified cognitive science of moral intuition. The book assumes evolution has furnished the human mind with two types of judgement: intuitive and deliberative. Focusing on moral intuitions (understood as moral judgments that were not arrived at via a process of conscious deliberation), the book explores the origins of these intuitions, examines how they are produced, and explains why the moral intuitions of different humans differ. Providing a unique synthesis of three separate established fields, this book presents a new research program that will further our understanding of the various different intuitive moral judgements at the heart of some of the moral tensions within human society.
Keywords: Ethics -- Psychological aspects; Philosophy and cognitive science; PHILOSOPHY / Ethics & Moral Philosophy; PSYCHOLOGY / Cognitive Psychology